3(x-4)+6=5(x-1)4

Simple and best practice solution for 3(x-4)+6=5(x-1)4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4)+6=5(x-1)4 equation:


Simplifying
3(x + -4) + 6 = 5(x + -1) * 4

Reorder the terms:
3(-4 + x) + 6 = 5(x + -1) * 4
(-4 * 3 + x * 3) + 6 = 5(x + -1) * 4
(-12 + 3x) + 6 = 5(x + -1) * 4

Reorder the terms:
-12 + 6 + 3x = 5(x + -1) * 4

Combine like terms: -12 + 6 = -6
-6 + 3x = 5(x + -1) * 4

Reorder the terms:
-6 + 3x = 5(-1 + x) * 4

Reorder the terms for easier multiplication:
-6 + 3x = 5 * 4(-1 + x)

Multiply 5 * 4
-6 + 3x = 20(-1 + x)
-6 + 3x = (-1 * 20 + x * 20)
-6 + 3x = (-20 + 20x)

Solving
-6 + 3x = -20 + 20x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-20x' to each side of the equation.
-6 + 3x + -20x = -20 + 20x + -20x

Combine like terms: 3x + -20x = -17x
-6 + -17x = -20 + 20x + -20x

Combine like terms: 20x + -20x = 0
-6 + -17x = -20 + 0
-6 + -17x = -20

Add '6' to each side of the equation.
-6 + 6 + -17x = -20 + 6

Combine like terms: -6 + 6 = 0
0 + -17x = -20 + 6
-17x = -20 + 6

Combine like terms: -20 + 6 = -14
-17x = -14

Divide each side by '-17'.
x = 0.8235294118

Simplifying
x = 0.8235294118

See similar equations:

| 0.81=logx | | 3x+10=3x-9 | | X^16+63=0 | | 81a^2-90ab+25b^2-16=0 | | 2(1.5c+4)=-4 | | 12x=-26 | | 3y^2-8=5y | | 2x+11=221 | | y=-5x^2+10 | | 1n+4n+9n=98 | | 72=2(2l)+2w | | 4x+12+15-3x=20-10 | | 3=2e^4x^2 | | 2z=14 | | -6a-10b=-30 | | 0.36(18)+0.04x=0.12(24+x) | | =1 | | -6m+6=-5m-3 | | 5r+7r=72 | | 5x-4x=55 | | 128=-16t^2+128t+2 | | 27x-7-18x=3(3x-3)+2 | | 7x+x=22 | | 3*(3+k)=48 | | -9+5p=7p-3 | | 10x+8y=183 | | 2.9x+58.4=12.0-8.7x | | 1.025x+2.458=7.582 | | 10(3t+1)-12=t(t+1) | | X^2+4+y^2+25=25 | | n+19=2n | | 18=b-9 |

Equations solver categories